Detecting Phenotypic and Genotypic of the Antibiotic Resistant Salmonella enterica Serotype Paratyphi Isolated from Blood Samples in Najaf Province /Iraq - Fadhil H.N. Al-Muhannak; Hashim Ali Abdualmeer Al-sherees; Ibrahim Abed Ali Abdul Sada; Thikra Abdullah Mahmood; Rasha Fadhel Obaid (مجلة الكوفة الطبية)
Background & Objectives: Salmonella Paratyphi is a leading cause of human paratyphoid fever in developing countries, causing deaths in humans worldwide. There are several paths for catching paratyphoid fever, but the close contact between patients and healthy humans is so far the most frequent cause of human infections. No study is found about the antibiotic resistance (phenotypic and genetic) of S. Paratyphi isolated from patients in Al-Najaf Province/Iraq, to the researcher’s best knowledge. Hence, this study aimed to determine the prevalence of S. Paratyphi isolates from blood specimens and the antibiotic resistance determinants of them, as well as the genetic relationship among isolates.